(untitled) (Revista de História da UEG (REVHIST), 2022)
This article aims to describe Auschwitz III – Monowitz and the Secret Anne from Is This a Man?, by Primo Levi, and the Anne Frank Diary, authored by the same, taking into account the type and moment of writing in both books. Thus, we will briefly discuss the concepts of memory, testimony and self-writing, based on the authors: Michael Pollak; Márcio Seligmann-Silva; José Antonio Zamora; Aremys Santos and Fernanda Andrade. As for the analysis of the sources, we used the historical-descriptive method, which allowed us to preserve and make a new record of Primo Levi’s testimony and Anne Frank’s personal records, both essential to understand Shoah by two different points of view. Emphasizing that this is a basic nature research, whose approach is qualitative and aims to produce knowledge about this topic of great importance and, at the same time, keeps alive the memory of the victims of Shoah. Keywords: Primo Levi. Anne Frank. Individual and collective memory. A testimony. Writing of you.